Paradigm Shift of Online English Language Platform as an Assessment Standard System - Saputra, Karin Sari; Halimi, Sisilia Setiawati; Anjarningsih, Harwintha Yuhria (JEES (Journal of English Educators Society), 2024)
Monitoring mechanisms are critical to the success of online English language learning programs, particularly where self - directed learning poses challenges to maintaining quality outcomes. This conceptual article introduces a paradigm shift in online language learning by proposing a standardized assessment framework to monitor learners’ progress. Through a theoretical analysis of existing online learning models, the article integrates insights from both humanistic technology and linguistic performance metrics to develop a new monitoring system. The proposed framework ensures consistent evaluation of learners’ knowledge, skills, and behaviors, tailored to the specific demands of online environments. The implications of this approach suggest that by incorporating standardized monitoring can significantly enhance learner engagement, accountability, and proficiency in online English platforms, thereby improving the overall quality of distance learning experiences. HIGHLIGHTS: Introduction of a standardized assessment framework: The study proposes a paradigmshift by integrating a standardized online assessment system to enhance the quality assuranceof English language learning platforms. Humanistic technology in language learning: The research highlights how digital platformsdriven by humanistic technology can effectively address the challenges of distance foreignlanguage learning. Improved student performance through monitoring mechanisms: Findings demonstratethat integrating pedagogical monitoring practices leads to measurable improvements inlearners’ language skills and engagement.